Water use of selected grain legumes in response to varying irrigation regimes - Chibarabada, Tendai P; Modi, Albert T; Mabhaudhi, Tafadzwanashe (Water SA, 2019)
Grain legumes have potential to contribute to food and nutritional security in water-scarce areas. Information on their yield, water use and water productivity (WP) would be useful for their promotion. The aim of the study was to make a comparative assessment of adaptation, yield, water use and WP of an African indigenous grain legume (bambara groundnut) and two major grain legumes (dry bean and groundnut) under rainfed, deficit and optimum irrigation conditions. Field trials were conducted during the 2015/16 and 2016/17 summer seasons in KwaZulu-Natal, South Africa, using a split-plot design arranged in completely randomised blocks with three replications. Data collected included stomatal conductance, leaf area index, timing of key phenological stages and yield. Water use was calculated as a residual of the soil water balance. Water productivity was obtained as the quotient of grain yield and water use. Crops adapted to limited soil water availability through stomatal regulation and reduction in canopy size and duration. Yield, yield components and WP varied significantly (P < 0.05) among crop species. During 2015/16, groundnut had the highest yield and WP (10 540 kg·ha−1 and 0.99 kg·m−3, respectively). During 2016/17, the highest yield and WP were observed in dry bean, 2 911 kg·ha−1 and 0.75 kg·m−3, respectively. For both seasons, dry bean had the lowest water use (143–268 mm) across all water treatments. Dry bean and groundnut out–performed bambara groundnut with respect to yield, harvest index and WP. For any promotion of bambara groundnut as an alternative crop, there is need for crop improvement to improve yield and WP.